The Green Deal, national energy and climate plans in Europe: Member states' compliance and strategies - Georgios Maris; Floros Flouros (Administrative Sciences, 2021)
This paper analyses the EU's policies for energy and climate, using Börzel's theoretical framework on Europeanisation, and examines Member States' Green Deal responses, strategies, and compliance. As expressed in their final NECPs, although Member States' responses vary, most of the critical components were partially addressed, while the others were largely addressed. We observe a considerable variation in Member States' strategies. Member States classified as foot-dragging beforehand are fence-sitting now, while those previously categorised as fence-sitting are now either foot-dragging or pace-setting. The root cause of these classification changes for the Member States within the EU can be traced back to their internal environments in which the involved stakeholders each have a different response pace regarding environment, climate, and energy. We present and analyse our theoretical context, discuss the EU's energy policies and the NECPs, examine Member States' responses and compliance with this new framework, and propose several challenges.
Keywords: 350; compliance; energy; environment; European Union; Green Deal; NECP; strategy